2022
DOI: 10.7759/cureus.25674
|View full text |Cite
|
Sign up to set email alerts
|

The Obesity Paradox in Chronic Heart Disease and Chronic Obstructive Pulmonary Disease

Abstract: Obesity in recent years has become an epidemic. A high body mass index (BMI) is one of today's most crucial population health indicators. BMI does not directly quantify body fat but correlates well with easier body fat measurements. Like smoking, obesity impacts multiple organ systems and is a major modifiable risk factor for countless diseases. Despite this, reports have emerged that obesity positively impacts the prognosis of patients with chronic illnesses such as chronic heart failure (CHF) and chronic obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 102 publications
0
11
0
Order By: Relevance
“…Early onset adiposity has been implicated in the pathogenesis of PCOS and can be predictive of a more severe phenotype. It is also linked to the development of low-grade inflammation, greater cardiometabolic dysfunction and future risk of atherosclerosis [12][13][14][15]. Our data shows that as an indicator of visceral fat function, VAI correlates well with severity of menstrual dysfunction and ovarian dysmorphology, and seems to be predictive of impaired glucose tolerance, thus indicating propensity for development of diabetes in the future.…”
Section: Discussionmentioning
confidence: 63%
“…Early onset adiposity has been implicated in the pathogenesis of PCOS and can be predictive of a more severe phenotype. It is also linked to the development of low-grade inflammation, greater cardiometabolic dysfunction and future risk of atherosclerosis [12][13][14][15]. Our data shows that as an indicator of visceral fat function, VAI correlates well with severity of menstrual dysfunction and ovarian dysmorphology, and seems to be predictive of impaired glucose tolerance, thus indicating propensity for development of diabetes in the future.…”
Section: Discussionmentioning
confidence: 63%
“…In recent years, evidence has shown that fat tissue accumulation may be bene cial to survival rate, which has become known as the "obesity paradox" [23]. Numerous studies have revealed that fat storage is a protective factor associated with lower mortality risk in patients with advanced CKD [24,25].…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Obesity, measured by the waist, hips, and body mass index (BMI) [ 8 ], is a significant risk factor for heart disease [ 4 , 9 ]. Approximately half of Americans (47%) have at least one of these obesity indicators, regardless of other sociodemographic, lifestyle, and clinical factors that increase the risk of heart disease [ 4 ].…”
Section: Introductionmentioning
confidence: 99%